A reading of 'place attachment' in spatial perception: The case of KTU department of architecture - Zafer İslam Taşdemir; Aslıhan Öztürk (Journal of Design for Resilience in Architecture and Planning)
The concept of space, the fundamental object of architecture, is perceived through sensory experiences, with prior spatial experiences playing a significant role in this process. Cultural diversity leads to variations in the spatial behavior of societies in different geographies, meaning that individuals experiencing the same structure may connect space, meaning, and place in diverse ways. This research builds upon Edward Relph’s Place and Placelessness, which examines the phenomenological dis-course on "how places are experienced and how they change." It focuses on the concept of "place attachment," defined as the emotional, cognitive, and behavioral bond formed at the intersection of the experiencing body and the experienced space. The Architecture Department at KTU, recognized for its accessibility and its role in training students proficient in architectural terminology and skilled in designing future spaces, has been selected as the focus of this study. The research aimed to derive semantic interpretations of the physical, emotional, and social dimensions of place, following the three categories Relph used in his analysis of place. A semi-structured interview technique with predetermined open-ended questions was employed, and participants were asked to create memory maps based on the building plan. Data analysis provided insights into how users perceived the study area, identifying spaces where a sense of attachment was strong. Conversely, areas perceived as "non-places," evoking a sense of being "out of place," were highlighted. Suggestions were offered for improving such negative spaces and guiding future research.